Transitioning From Master's Studies to the Classroom: From Theory to Practice. Issue 3 (1st April 2019) - Hennebry‐Leung, Mairin; Gayton, Angela; Hu, Xiao Amy; Chen, Xiaohui
Abstract : The importance of social interaction in a community of practice for promoting effective teacher learning is well established (Johnson & Golombek, 2011; Lave & Wenger, 1991). Research outlines the challenges language teachers experience in transitioning between teacher education programmes and the classroom, particularly regarding the theory–practice nexus, and emphasizes the professional community's key role in providing mentoring and support. In this regard, language teachers' experiences in transitioning from theoretically oriented language education master's programmes to the language classroom are underresearched. This study reports data gathered from 21 mainland Chinese participants transitioning from master's programmes in three locations (Hong Kong, Scotland, and China) to language classrooms in China. In line with other research on teacher education programmes, this study's findings suggest interesting common experiences among these new teachers regardless of the context where their studies took place, including a sense of isolation, a "sink‐or‐swim" phenomenon leading to the abandonment of theoretically grounded pedagogical beliefs in exchange for adherence to "safe" practice, confusion regarding the relationship between learning on university programmes and the practice of teaching, and weak self‐efficacy as transitioning teachers face internal and external pressures. Implications and consequences are discussed in the context of the theory–practice nexus.